Yolk–Shell Fe/Fe4N@Pd/C Magnetic Nanocomposite as an Efficient Recyclable ORR Electrocatalyst and SERS Substrate. Issue 7 (16th January 2019) - Jiao, Wenling; Chen, Chen; You, Wenbin; Zhang, Jie; Liu, Jiwei; Che, Renchao
Abstract: A yolk–shell Fe/Fe4 N@Pd/C (FFPC) nanocomposite is synthesized successfully by two facile steps: interfacial polymerization and annealing treatment. The concentration of Pd 2+ is the key factor for the density of Pd nanoparticles (Pd NPs) embedded in the carbon shells, which plays a role in the oxygen reduction reaction (ORR) and surface‐enhanced Raman scattering (SERS) properties. The ORR and SERS performances of FFPC nanocomposites under different concentrations of PdCl2 are investigated. The optimal ORR performance exhibits that onset potential and tafel slope can reach 0.937 V (vs reversible hydrogen electrode (RHE)) and 74 mV dec −1, respectively, which is attributed to the synergistic effects of good electrical conductivity, large electrochemically active areas, and strong interfacial charge polarization. Off‐axis electron holography reveals that interfacial charge polarization could facilitate the ORR of Pd NPs and defective carbon simultaneously and the shell with low density of Pd NPs is easier to form strong interfacial charge polarization. Moreover, FFPC‐3 with maximum EF of 2.3 × 10 5 results from more hot‐spots, local positive charge centers to attract rhodamine 6G molecules, and magnetic cores. This work not only offers a recyclable multifunctional nanocomposite with excellent performance, but also has instructional implications for interfacial engineering for electrocatalysts design. Abstract : Yolk–shell Fe/Fe4 N@Pd/C (FFPC) multifunctional nanocomposite is synthesized as an efficient recyclable oxygen reduction reaction (ORR) electrocatalyst and surface‐enhanced Raman scattering (SERS) substrate. By tuning the concentration of PdCl2, the ORR and SERS performances of FFPC nanocomposite are optimized. Moreover, the mechanism of the enhanced ORR and SERS performances of FFPC nanocomposite is proposed, revealed by off‐axis electron holography.